Homicide trends in Finland and Estonia in 1880-1940: Consequences of the demographic, social and political effects of industrialization - Lehti, Martti (Journal of Scandinavian studies in criminology and crime prevention, 2001)
While in western Europe and Scandinavia homicide rates reached their all time low during the period of industrialization, in Finland and Estonia they increased considerably. The rapid growth of criminal violence during the late 1800s and first half of the 1900s in these two countries seems to have been the result of interaction of several factors, partly non-simultaneous and unrelated. They do not seem to have been identical either, although the underlying equation was the same: the quick social and economic change following industrialization, and the modernisation of agriculture, the pressures it put especially on the youth in the form of uncertain prospects for the future and a new competition-oriented set of values, connected with the authoritarian political system of Russian Empire, which prevented necessary political reforms and left behind a legacy of social thinking idealizing violence as a political and social instrument. A legacy, which affected large parts of Finnish and Estonian population still for years after the czarist system itself already passed into history. The criminal violence arisen from the equation, however, had quite a different face on the northern coast of the Gulf of Finland from that on the southern one. In Finland the violence was centered in the new forest industrial communities, in Estonia again among the landless population of the countryside